Alternatif Herbal untuk Menurunkan Demam : Efektivitas Ekstrak Daun Sirih (Piper betle) Dibandingkan Parasetamol - Haryanto Haryanto; Fitrinaya Fitrinaya (Lembaga Pengembangan Kinerja Dosen, 2025)
Fever is a condition characterized by an increase in body temperature as a response to infection or inflammation, and it is one of the most common clinical symptoms in various diseases. The excessive use of synthetic antipyretics such as paracetamol can lead to side effects; therefore, safer and natural-based alternatives are needed. This study aims to determine the antipyretic activity of betel leaf and to compare its effectiveness with that of paracetamol.This research was conducted using an experimental laboratory method with a completely randomized design. The test subjects were male white rats (Rattus norvegicus) of the Wistar strain, induced with fever using a 20% yeast suspension. The rats were divided into five groups: negative control, positive control (paracetamol), and three treatment groups with low, medium, and high doses of the extract. Body temperature was measured every 30 minutes for 180 minutes after treatment. The data were statistically analyzed using one-way ANOVA followed by Tukey's post hoc test.The results showed that the [plant extract] exhibited significant antipyretic activity (p < 0.05) compared to the negative control, especially at medium and high doses. The effectiveness of the highest dose was comparable to that of paracetamol. This antipyretic effect is presumed to be associated with the presence of flavonoids and tannins that may inhibit the synthesis of prostaglandin E2 (PGE2), a key mediator in the fever response.In conclusion,betel leaf has potential as an effective natural antipyretic agent and may be developed as a safer herbal-based alternative for fever treatment.